Tree tobacco (Nicotiana glauca) cuticular wax composition is essential for leaf retention during drought, facilitating a speedy recovery following rewatering. Issue 5 (7th December 2022) - Negin, Boaz; Hen‐Avivi, Shelly; Almekias‐Siegl, Efrat; Shachar, Lior; Jander, Georg; Aharoni, Asaph
Summary: Despite decades of extensive study, the role of cuticular lipids in sustaining plant fitness is far from being understood. We utilized genome‐edited tree tobacco ( Nicotiana glauca ) to investigate the significance of different classes of epicuticular wax in abiotic stress such as cuticular water loss, drought, and light response. We generated mutants displaying a range of wax compositions. Four wax mutants and one cutin mutant were extensively investigated for alterations in their response to abiotic factors. Although the mutations led to elevated cuticular water loss, the wax mutants did not display elevated transpiration or reduced growth under nonstressed conditions. However, under drought, plants lacking alkanes were unable to reduce their transpiration, leading to leaf death, impaired recovery, and stem cracking. By contrast, plants deficient in fatty alcohols exhibited elevated drought tolerance, which was part of a larger trend of plant phenotypes not clustering by a glossy/glaucous appearance in the parameters examined in this study. We conclude that although alkanes have little effect on whole N. glauca transpiration and biomass gain under normal, nonstressed conditions, they are essential during drought responses, since they enable plants to seal their cuticle upon stomatal closure, thereby reducing leaf death and facilitating a speedy recovery.